The influence of the board commissioners’s characteristics on conservatism with gender as a moderating variable - Trisnayanti, Ida Ayu Ivon; Wirama, Dewa Gede; Ratnadi, Ni Made Dwi; Gayatri, Gayatri (International research journal of management, IT and social sciences, 2022)
Accounting conservatism can limit the opportunistic behaviour of managers who act to maximize their interests. One of the good corporate governance mechanisms, which is the characteristics of the board of commissioners, can strengthen the implementation of conservatism in the company. In this study, researchers wanted to examine the effect of independent commissioners and audit committees on conservatism with gender as a moderating variable. The research population is publicly listed companies on the Indonesia Stock Exchange during 2015-2019. The sampling technique used is purposive sampling. Research testing uses moderated regression that has model feasibility is tested with the classical assumption test. The results showed that conservatism increased with the presence of an audit committee. The audit committee can provide specific suggestions to be more conservative in making decisions. However, the results showed that conservatism was not affected by the proportion of independent commissioners. The results also show that the presence of women strengthens the relationship of the audit committee to conservatism.